Weightlifting - Chavda, S.; Everett, G. (Routledge handbook of strength and conditioning: Sport-specific programming for high performance, 2018)
The sport of weightlifting requires high amounts of muscular power, strength and skill. It is evident that the most successful weightlifters are able to display a rearward movement of the bar during the 1st pull, creating a steady bar velocity which increases exponentially during the And pull. This allows the lifter to keep the bar close to the body and transfer mechanical energy to the bar, thus contributing to greater vertical bar displacement, allowing the lifter sufficient time to drop under and receive the bar in the catch. The primary contributing factors to these pre- ferred bar kinetics and kinematics stem from greater work being carried out during the ist pull with a decrement evident during the 2nd pull; however, power production is far greater during the 2nd pull as a result of an increase in hip, knee and ankle angular displacement, furthered by a contribution of the stretch reflex. Weightlifting has shown high levels of injury rates when compared to other Olympic sports, particularly in the elbow, but this may be due to individuals attempting higher loads than usual with more at stake. Injury rates in training are typically experienced in the lower back; they tend to be acute in nature and result in a loss of less than one day of training. Commonly strains are the most experienced type of injury, and are typically down to over use, thus showing the importance of organising rest days and variability into the program. In terms of programming we must consider the exercise selection, volume and intensity prescribed at different periods, namely the preparatory and competitive phase. Typically, greater assistance and strength work will be performed during the preparatory phase with a greater emphasis on squatting and pulling strength, whereas the competitive phase would focus on maintaining these strength qualities and transferring them to the competitive lifts, ready for competition. With weightlifting being multifactorial in nature, one can enhance the chance of success by understanding the key technical aspects of the lifts and the exercises associated with their development. We therefore suggest that adaptations should be made in one`s physical condition and capabilities, as the ability to perform the competitive lifts with appropriate competency will ensure the greatest chance of success in the future.